Structuring contexts: pathways toward un-obstructing race-consciousness. Issue 8 (13th September 2016) - Berchini, Christina
Abstract: This research is situated in second-wave White Teacher Identity studies and investigates the ways context structures a high school English teacher's white identity, practices, and race-consciousness. Working with detailed data and vignettes from a single case study, the author highlights the teaching of a unit on the Holocaust. Using the required Holocaust curriculum as a unit of analysis, the author illustrates how the teacher is structured to minimize and dismiss broader discussions of institutionalized and systemic oppression and violence, and particularly those contributions offered by a student of color in her classroom. The author argues that understanding the role contexts play in obstructing race-consciousness can help fill interpretive gaps between race-conciousness and what, on the surface, might appear to be a teacher's race-evasiveness.